The role of midwife in health promotion and diseases diseases prevention - Kawałek, Kinga; Korda, Aleksandra; Klimek, Wiktoria; Kupińska, Justyna; Ślusarska, Barbara; Iwanowicz-Palus, Grażyna; Bień, Agnieszka (Journal of Education, Health and Sport, 2017)
Introduction: Providing education and health activities by midwife in terms of preparing women for childbirth, puerperium, breastfeeding, parenting and also educational tasks in the area of healthy lifestyle and early diagnostics of female illnesses are a wide range of health services. <span style="font-size: 12pt; line-height: 150%; color: #222222; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" lang="EN-US">Objective: <span style="font-size: 12pt; line-height: 150%; color: #222222; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" lang="EN-US">The aim of the study is to define a scope and characteristics of health promotion and diseases prevention in professional practice based on the midwives experience. The survey was carried out in focus group of 13 midwives, who in their professional practice realize health education among women. Research material was collected in 2017. <span style="font-size: 12pt; line-height: 150%; color: #222222; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" lang="EN-US">Results: <span style="font-size: 12pt; line-height: 150%; color: #222222; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" lang="EN-US">Midwives had a diversified work experience between 1 year and 35 years. The recipients of health services provided by midwives were women of all ages, including mostly pregnant, postpartum and postmenopausal women, as well as premature children parents. Generally midwives in their experience syndicated taking part in profhylactic programs in their workplaces. It was especially prevention of cervical cancer and breast cancer. Important part of health promotion in midwives experiences were promotion of natural breastfeeding, lacteal counseling and education about newborn vaccination. <span style="font-size: 12pt; line-height: 150%; color: #222222; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" lang="EN-US">Conclusion: <span style="font-size: 12pt; line-height: 150%; color: #222222; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" lang="EN-US">Collected data shows that leading prophylactic programs and health promotion applies in midwives’ every day work. Too little time to implement health promotion and education is a factor hindering the work of midwives.